Ensuring Beverage Excellence: A Quality Control Guide - Swetha Vasudevan; Jeevitha Gada Chengaiyan (Food Science and Engineering, 2024)
In the food industry, beverage is one of the important sectors that includes various alcoholic and non-alcoholic beverages. The quality of raw materials, equipment, and satisfaction of consumers are the important factors that determine the quality of the beverage manufacturing system. The nonfulfillment of any of the aforementioned factors can lead to the rejection of goods by consumers. This review paper provides a comprehensive examination of beverage quality control and addresses the various challenges faced by the beverage industry. The critical role of water quality in beverage production and the diverse quality attributes encompassing microbiological, physicochemical, and organoleptic characteristics are thoroughly discussed. The microbial contamination and poor product quality like off-flavor, unpleasant smell, and textural changes result in product recall. The quality of beverages can be ensured by sequential assessment of raw material quality, the process of production and packaging, microbial assessment, and sensorial attributes. The review also explores novel approaches such as biosensors, electronic tongues and noses, smart packaging, and the application of artificial intelligence and machine learning to address these issues. These developments provide novel solutions to ensure the quality and safety of products.